THE CLIMATE CHANGE IN MEDIA: A CONCEPTUAL METAPHOR ANALYSIS (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article explores a conceptual metaphor analysis of the image of the climate change in media. Climate change has become one of the most pressing global challenges, and media plays a crucial role in shaping public perceptions and attitudes towards this issue. Metaphors, as important linguistic tools in media communication, are employed to simplify complex ideas and elicit emotions. This study aims to examine the conceptual metaphors employed in media representations of the climate change and their implications for public understanding and engagement. Through a comprehensive analysis of media texts, including news articles, opinion pieces, and visual imagery, this study identifies and interprets the dominant metaphors used to depict the climate change. The findings highlight the role of metaphors in influencing public discourse, shaping policy discussions, and ultimately influencing collective efforts for climate change mitigation and adaptation